A Review of Computational Electromagnetic Methods for Graphene Modeling - Yu Shao; Jing Jing Yang; Ming Huang (International Journal of Antennas and Propagation)
Graphene is a very promising optoelectronic material and has gained more and more attention. To analyze its electromagnetic properties, several numerical methods have been developed for graphene simulation. In this paper, a review of application of graphene in electronic and photonic device is provided, as well as some widely used computational electromagnetic algorithms for graphene modeling. The advantages and drawbacks of each method are discussed and numerical examples of these methods are given to illustrate their performance and application.